2015
DOI: 10.1159/000440810
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index below Obesity Threshold Implies Similar Cardiovascular Risk among Various Polycystic Ovary Syndrome Phenotypes

Abstract: Objective: The aim of this study was to determine the cardiometabolic risk factors in different polycystic ovary syndrome (PCOS) phenotypes. Subjects and Methods: This cross-sectional study was performed between 2010 and 2011. Eighty-nine patients with PCOS and 25 age- and weight-matched healthy controls were included in the study. Patients were grouped using the Rotterdam 2003 criteria as: group 1, oligomenorrhea and/or anovulation (ANOV) and hyperandrogenemia (HA) and/or hyperandrogenism (n = 23); group 2, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…The median value of BMI in four phenotypes was rather low, which could be associated with young age of patients. The study conducted by Bagir et al [49] showed higher mean values of BMI (for phenotype 1-27.9 ± 7.5, for phenotype 2-26.1 ± 5.3, for phenotype 3-24.3 ± 4.2, and for phenotype 4-27.9 ± 5.2), even if the mean age was similar to that in our study. Our results also suggest that the relationship between high BMI and individual phenotypic features of the Rotterdam criteria that characterize PCOS remains unclear, as was claimed by Neubronner et al [50].…”
Section: Discussionsupporting
confidence: 82%
“…The median value of BMI in four phenotypes was rather low, which could be associated with young age of patients. The study conducted by Bagir et al [49] showed higher mean values of BMI (for phenotype 1-27.9 ± 7.5, for phenotype 2-26.1 ± 5.3, for phenotype 3-24.3 ± 4.2, and for phenotype 4-27.9 ± 5.2), even if the mean age was similar to that in our study. Our results also suggest that the relationship between high BMI and individual phenotypic features of the Rotterdam criteria that characterize PCOS remains unclear, as was claimed by Neubronner et al [50].…”
Section: Discussionsupporting
confidence: 82%
“…Several studies, mostly regarding East Asian and South Asian populations, reported highest prevalence of phenotype IV. [11][12][13][14][15][16][17][18][19] Three Turkish studies [20][21][22] reported similar prevalence of all four phenotypes. The average overall prevalence of the four PCOS phenotypes in different ethnic groups is shown in Figure 2.…”
Section: The Prevalence Of Pcos Phenotypesmentioning
confidence: 99%
“…Insulin also augments the thecal androgen production responsible for acne and hirsutism . In the longer term, hyperinsulinaemia increases the risks of diabetes (type II and gestational), coronary heart disease and endometrial cancer .…”
Section: Introductionmentioning
confidence: 99%